The Impact of Obesity on Mental Health in Adolescents - Siti Syamsiah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescent obesity is a global health issue that continues to rise, particularly among teenagers, with potentially adverse effects on both physical and mental health. The physical impacts of obesity can trigger various mental health problems, such as stress, depression, anxiety, and low self-esteem. Obese adolescents often face social stigma and environmental pressures, which further exacerbate their psychological conditions. This study aims to explore the relationship between obesity and mental health among adolescents in Koja, North Jakarta, and to identify the prevalence of mental health issues within this group. Specifically, the research seeks to analyze the correlation between Body Mass Index (BMI) and mental health parameters, such as stress, anxiety, and depression; investigate the prevalence and severity of mental health disorders in obese adolescents in the region; identify additional factors, such as social support and dietary patterns, that may influence the mental health of obese adolescents; and provide evidence-based recommendations for targeted interventions that integrate weight management and psychological support to improve adolescent mental health and overall well-being. The study employs a quantitative approach with a cross-sectional design. Data were collected from 55 adolescents aged 12–18 years with a BMI ≥ 25 kg/m² using questionnaires. Mental health was assessed using the DASS (Depression, Anxiety, and Stress Scale), and data analysis was conducted using Pearson correlation tests. The results revealed a positive correlation between obesity and mental health issues. A total of 60% of respondents experienced high levels of stress, 45% exhibited symptoms of anxiety, and 30% reported mild to moderate depression. Adolescents with higher BMI scores tended to have higher DASS scores. Other factors, such as social support and dietary patterns, also influenced their mental well-being. Adolescent obesity in Koja, North Jakarta, is strongly associated with mental health issues, such as stress, anxiety, and depression. Holistic intervention programs are essential, including weight management, psychological support, and social assistance, to improve the quality of life for adolescents.